2007
DOI: 10.7557/2.27.4.320
|View full text |Cite
|
Sign up to set email alerts
|

George’s Island, Labrador - A high-density predator-free refuge for a woodland caribou subpopulation?

Abstract: The movement patterns and demographic parameters were measured for caribou (Rangifer tarandus caribou) on George’s Island (Labrador, Canada) to determine if the population is separate from the Mealy Mountain Caribou Herd. Movements between George’s Island caribou and nearby Mealy Mountain caribou were examined through satellite telemetry (April 2005 to April 2006). Demographic information was collected through aerial classification surveys. The predator-free island is currently maintaining a density of 22.5-26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our research demonstrates that wildlife management must consider these other bodies of knowledge to understand how being ignored or not being heard "impacts how the past resonates in the present" [66]. Our research also highlights the diversity of ways of knowing and being with Mealy Mountain Caribou and for caribou management (i.e., ontological pluralism) [67], and illustrates that wildlife management strategies need to reflect the plurality of knowledge systems, perspectives, and ways of knowing, doing, and being for stronger health outcomes for both humans and animals.…”
Section: Discussionmentioning
confidence: 75%
“…Our research demonstrates that wildlife management must consider these other bodies of knowledge to understand how being ignored or not being heard "impacts how the past resonates in the present" [66]. Our research also highlights the diversity of ways of knowing and being with Mealy Mountain Caribou and for caribou management (i.e., ontological pluralism) [67], and illustrates that wildlife management strategies need to reflect the plurality of knowledge systems, perspectives, and ways of knowing, doing, and being for stronger health outcomes for both humans and animals.…”
Section: Discussionmentioning
confidence: 75%
“…The low density of predators throughout the archipelago is therefore an unlikely driver of swimming in our system, though predation may still influence swimming behavior for caribou elsewhere in their range (e.g., Jeffery et al. 2007).…”
Section: Figmentioning
confidence: 99%
“…Even for adept swimmers like caribou (Rangifer tarandus), which have hollow hair shafts that aid in flotation, the energetic expenditure of swimming for terrestrial mammals is markedly higher than walking or running (Miller and Gunn 1985). The drivers that promote the decision to swim for terrestrial mammals, like caribou, are often related to the profitability of forage (Miller et al 1977) and the risks of predation (Jeffery et al 2007, Jordan et al 2010. The Fogo Island archipelago, off the coast of Newfoundland, Canada, is home to approximately 300 woodland caribou, descendants of 26 individuals introduced from the Island of Newfoundland to Fogo Island between 1964 and 1967 (Bergerud and Mercer 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because it has been suggested that the MMCH is divided into a mainland subpopulation and an island subpopulation in which individuals are thought to only inhabit George Island, a 12 km 2 island located 9 km offshore from the herd's range (Jeffery et al 2007), the telemetry data from both of these putative subpopulations were examined closely. To quantify fidelity inter-year distances between previous year locations were computed to examine annual profiles of the tendency to return to the same site (Schaefer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%